2022
DOI: 10.1037/xhp0001043
|View full text |Cite
|
Sign up to set email alerts
|

Concurrently observed actions are represented not as compound actions but as independent actions.

Abstract: Recent research suggests that we can simultaneously represent the actions of multiple agents in our motor system. However, it is unclear exactly how concurrently observed actions are represented. Here, we tested two competing hypotheses. According to the independence hypothesis, concurrently observed actions are represented as independent actions. According to the compound hypothesis, they are instead integrated, whenever possible, into compound actions. In Experiment 1 (N = 32), we first show that the standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Our present results are also in line with other recent evidence in favor of action Gestalten: When a certain single response [A] is more frequently practiced, this practice does not appear to transfer to allow for an easier execution of the A-part of dual [A + B] responses 50 . In addition, recent research on action imitation showed that executing a dual action (lifting both index and middle finger) is facilitated by observing a corresponding dual action but not by seeing the two composite actions (i.e., one stimulus hand lifts the index finger while another stimulus hand lifts the middle finger) 51 . Note that while our present study still involves rather basic actions, we believe that similar Gestalt representation formats occur as task complexity increases (especially in complex body movements such as dancing).…”
Section: Discussionmentioning
confidence: 99%
“…Our present results are also in line with other recent evidence in favor of action Gestalten: When a certain single response [A] is more frequently practiced, this practice does not appear to transfer to allow for an easier execution of the A-part of dual [A + B] responses 50 . In addition, recent research on action imitation showed that executing a dual action (lifting both index and middle finger) is facilitated by observing a corresponding dual action but not by seeing the two composite actions (i.e., one stimulus hand lifts the index finger while another stimulus hand lifts the middle finger) 51 . Note that while our present study still involves rather basic actions, we believe that similar Gestalt representation formats occur as task complexity increases (especially in complex body movements such as dancing).…”
Section: Discussionmentioning
confidence: 99%